2017
DOI: 10.1007/s11214-017-0343-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimations of the Seismic Pressure Noise on Mars Determined from Large Eddy Simulations and Demonstration of Pressure Decorrelation Techniques for the Insight Mission

Abstract: International audienceThe atmospheric pressure fluctuations on Mars induce an elastic response in the ground that creates a ground tilt, detectable as a seismic signal on the InSight seismometer SEIS. The seismic pressure noise is modeled using Large Eddy Simulations (LES) of the wind and surface pressure at the InSight landing site and a Green’s function ground deformation approach that is subsequently validated via a detailed comparison with two other methods: a spectral approach, and an approach based on So… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(110 citation statements)
references
References 26 publications
5
105
0
Order By: Relevance
“…In order to make a sanity check, we have also developed a quasi-static model using Green's function approach: a pressure field applies in a static way on a homogeneous half-plane. This simpler model gives very similar results, as described in Murdoch et al (2016a). The advantage of this simpler model is that it can be considered as validated on Earth: Lorenz et al (2015) has shown that the size and amplitude of seismic signal generated on a seismometer by a dust devil (which can be assimilated to a pressure point source) can be measured, and is consistent with the Greens' function approximation used.…”
Section: Pressure Field Assumptionsmentioning
confidence: 55%
See 4 more Smart Citations
“…In order to make a sanity check, we have also developed a quasi-static model using Green's function approach: a pressure field applies in a static way on a homogeneous half-plane. This simpler model gives very similar results, as described in Murdoch et al (2016a). The advantage of this simpler model is that it can be considered as validated on Earth: Lorenz et al (2015) has shown that the size and amplitude of seismic signal generated on a seismometer by a dust devil (which can be assimilated to a pressure point source) can be measured, and is consistent with the Greens' function approximation used.…”
Section: Pressure Field Assumptionsmentioning
confidence: 55%
“…The correlation with a local measurement of the pressure variation can, therefore, be questioned. Murdoch et al (2016a) demonstrate that the local tilt is well correlated with the local pressure measurement up to a distance of 1 to 4 km depending on the wind conditions (windier conditions induce a better correlation). By using the synthetic noise data obtained from the LES pressure field, we were able to demonstrate that our decorrelation approach is efficient, resulting in a reduction by a factor of ∼5 observed in the horizontal tilt noise (in the wind direction) and the vertical noise.…”
Section: Pressure Field Decorrelationmentioning
confidence: 73%
See 3 more Smart Citations